In, against, and beyond capitalism : the San Francisco lectures - Holloway, John, 1947- (Kairos, 2016)
An accessible venture into the thinking of John Holloway and his unique take on left radical theory In, Against, and Beyond Capitalism is based on three recent lectures delivered by John Holloway at the California Institute of Integral Studies in San Francisco. The lectures focus on what anticapitalist revolution can mean todayu2014after the historic failure of the idea that the conquest of state power was the key to radical change. The first lecture focuses on the meaning of "We," the second on the understanding of capital as a system of social cohesion that systematically frustrates our creative force, and the third on the proposal that we are the crisis of this system of cohesion. In addition, it includes an introductory preface by Andrej Grubacic, the Q & A after each lecture, and a bibliographic essay by the author.